(untitled) (Fiep Bulletin - online, 2015)
This institution created to from the Teachers of Physical Education for both sexes as well as Home Education Teachers of the Republic of Chile, Will be 50 years old by next March. It belongs to the Faculty of Philosophy and Education depending from the University of Chile, having at present a register of about 300 pupils.